Domination in Generalized Cayley Graph of Commutative Rings (Journal of Mathematical Study, 2021)
Let $R$ be a commutative ring with identity and $n$ be a natural number. The generalized Cayley graph of $R$, denoted by $Γ^n_R$, is the graph whose vertex set is $R^n$\{0} and two distinct vertices $X$ and $Y$ are adjacent if and only if there exists an $n×n$ lower triangular matrix $A$ over $R$ whose entries on the main diagonal are non-zero such that $AX^T=Y^T$ or $AY^T=X^T$, where for a matrix $B$, $B^T$ is the matrix transpose of $B$. In this paper, we give some basic properties of $Γ^n_R$ and we determine the domination parameters of $Γ^n_R$.
Keywords: Ring; Cayley graph; generalized Cayley graph; domination number.